Designing local network structure for distributed computer system of real time; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 5 - Pogrebnoy A. V. Aleksandr Vladimirovich (Control, computer engineeringand information science, 2007)
Заглавие с титульного листа